Putative Blood Biomarkers on Tropical Resilience in Philippine Native and Crossbred Heifers - Pandangan, E. M. I.; Dominguez, J. M. D.; Turaja, K. I B.; Guadayo, G. F.; Sumaya, N. H. N.; Tabugo, S. R. M.; Del Barrio, A. N.; Kim, K. S.; Moneva, C. S. O. (Tropical Animal Science Journal, 2026)
Hematological values are essential in understanding the health of an animal. Interpretation of these values must consequently be clinically accurate. These values are also putative biomarkers for resiliency under tropical conditions. In this study, blood profiles of Panay Native (PN) and crossbred Holstein x Jersey (HxJ) heifer cattle were compared to identify biomarkers of tropical resilience. Blood samples from 58 heifers were analyzed using General Linear Models and multivariate techniques. Results demonstrated that temperate-derived Reference Intervals frequently misclassified healthy animals. The Panay cattle exhibited a superior erythropoietic phenotype (significantly higher RBC, HGB, PCV, p<0.001), driven by a unique regulatory mechanism in which increased red cell counts were balanced by reduced cell volume (negative RBC-MCV correlation, r = -0.76, p<0.001). In contrast, crossbred heifers exhibited signs of compensated hemolysis, characterized by regenerative anemia (>55% prevalence). Multivariate analysis revealed a clear divergence in physiological strategies, with crossbred cattle displaying a trade-off between erythropoiesis and immune stability, whereas the native cattle demonstrated superior homeostatic stability. Overall, this study confirms that non-localized reference intervals misinterpret the physiological realities of tropical herds, causing systemic diagnostic errors. Furthermore, the unique regulatory patterns substantiate the ’viscosity clamp’ or the uncoupling of cell count and volume as putative biomarkers of innate climate resilience in indigenous cattle.